What’s in a “Smile?” Intra-operative Observations of Contralateral Smiles Induced by Deep Brain Stimulation - Okun, Michael S. (Neurocase, 2004)
OBJECTIVE: To describe smiling and euphoria induced by deep brain stimulation (DBS). BACKGROUND AND SIGNIFICANCE: The brain systems inducing emotional experiences and displays are not entirely known, but the ventral striatum including the nucleus accumbens has been posited to play a critical role in mediating emotions with positive valence. DBS has been successfully employed for the treatment of movement disorders, and most recently obsessive compulsive disorder (OCD). The purpose of this report is to describe the emotional changes associated with stimulation of the ventral striatum. METHODS: A single patient with intractable OCD had electrode arrays placed in the right and left anterior limbs of the internal capsule and region of the nucleus accumbens. Changes in facial movement during stimulation were quantified by video recording. Ten video segments, time locked to the onset of stimulation, were digitized and changes in pixel intensity that occurred over both sides of the lower face, on a frame by frame basis, following stimulation onset were computed. These summed changes in pixel intensity represented the dependent variable of “entropy” and directly corresponded to changes in light reflectance that occur during facial movement. RESULTS: During stimulation on both the right and left side, the patient consistently developed a half smile on the side of the face contralateral to the stimulating electrode, and also became euphoric. The effect ceased when DBS was discontinued. CONCLUSIONS: DBS in the region of the nucleus accumbens produced smile and euphoria suggesting that alterations in the ventral striatum may result in emotional experience and displays. We hypothesize the existence of a limbic-motor network responsible for such changes. This observation suggests that DBS may be useful as a therapy for mood disorders.